Strategies to manage the ethnic diversity in Sri Lanka: Social cohesion through education - Ramzy, Mohammad Ismath; Ashaari, Muhamad Faisal (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
Diversity has become a challenge in many communities for their socioeconomic and political development. Overlooking the positives benefits of diversity, considerable attention has been given to negative aspect instead. Hence, there is a potential to build a rich civilization through proper management of diversity. Education plays a key role in managing the diversity by enhancing social identity of children. Hence, this research aims at explaining the strategies and plans adopted by the education ministry in Sri Lanka to promote social cohesion and exploring the challenges that faced by the decision makers in implementing these strategies and plans in schools. For this purpose, the present study employed a qualitative research methodology based on textual and document analysis along with open-ended interview protocol. Nine people who are in decision-making position in the process of implementation in different levels; national, provincial, zonal and school were selected for the interview. This research used interviews, textual and document analysis to collect the data. Curtailment of cultural acceptance, insufficient awareness on multiculturalism, segregated system of schooling; inadequate trained-teachers and poor coordination were found in this study as major challenges to promote social cohesion through education. This research recommends addressing these issues prior to implement the strategies on social cohesion in order to maximize the result.